2019
DOI: 10.3389/fnana.2019.00007
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Multi-Beam Light-Sheet Fluorescence Microscope for Live Imaging Without Striping Artifacts

Abstract: The development of light-sheet fluorescence microscopy (LSFM) has greatly expanded the experimental capabilities in many biological and biomedical research fields, enabling for example live studies of murine and zebrafish neural activity or of cell growth and division. The key feature of the method is the selective illumination of a sample single plane, providing an intrinsic optical sectioning and allowing direct 2D image recording. On the other hand, this excitation scheme is more affected by absorption or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…In summary, we have implemented an AOD-based dual Gaussian beam excitation system capable of single-and dualvirtual slit confocal LSFM. AODs allow inertia-free MHz scan rates and the generation of multiple sheets with independent spatial and amplitude control, 21 which can be easily synchronized with any single-or dual-rolling shutter readout mode of an sCMOS camera. We have demonstrated that the dual-confocal detection regime achieves a twofold improvement in imaging speed, in respect to traditional confocal LSFM, without any negative impact on the contrast, at the very least in the case of samples with small background levels such as optically cleared tissues or zebrafish larvae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, we have implemented an AOD-based dual Gaussian beam excitation system capable of single-and dualvirtual slit confocal LSFM. AODs allow inertia-free MHz scan rates and the generation of multiple sheets with independent spatial and amplitude control, 21 which can be easily synchronized with any single-or dual-rolling shutter readout mode of an sCMOS camera. We have demonstrated that the dual-confocal detection regime achieves a twofold improvement in imaging speed, in respect to traditional confocal LSFM, without any negative impact on the contrast, at the very least in the case of samples with small background levels such as optically cleared tissues or zebrafish larvae.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we used this AOD capability to demonstrate the simultaneous generation and control of multiple beams to attenuate striping artifacts present in LSFM images. 21 In this letter, we report on the use of an AOD in the illumination path of a DLSM to independently generate two Gaussian beams and sweep them across the FOV synchronously with any double rolling shutter readout direction of an sCMOS camera, resulting in a twofold peak frame-rate speed-up in the confocal detection regime, without loss of contrast. We apply this high-speed CLSFM to explore the mouse brain structure with subneuron resolution and to record zebrafish larvae's brain activity, which are typical LSFM applications.…”
Section: Introductionmentioning
confidence: 99%
“…Like in most 2P designs, our use of a Gaussian beam does not permit the generation of a truly arbitrary PSF shape. Nevertheless, if used in combination with temporal focussing (SchrĂśdel et al 2013;Weisenburger et al 2019) it would, in principle, be possible to modulate axial PSF expansion without strongly affecting lateral expansion, thus facilitating a greater range of PSF shapes. Similarly, an optimized design of the objective lens (Negrean & Mansvelder 2014) and other optical elements (Bumstead 2018) including the use of large diameter lenses to minimize aberrations (Tsai et al 2015), could all be combined with our optical design to further enhance the quality of 2P excitation.…”
Section: Discussionmentioning
confidence: 99%
“…However, at 7 dpf the brain is ~1.2 mm long and therefore too large to fit into the FOV of a typical DL 2P setup. Instead, its transparent body wall makes larval zebrafish well-suited for 1-photon selective-plane-illumination microscopy (1p-SPIM / "lightsheet microscopy"), which is not FOV-limited in the same way as 2P microscopy (Ahrens et al 2013;Fahrbach et al 2008;Sancataldo et al 2019). However, 1p-SPIM and related techniques (Huisken & Stainier 2009) have a number of drawbacks, including constraints on achieving a homogenous image due to scattering and divergence of the excitation light with increasing lateral depth (Weisenburger & Vaziri 2018), limited access to tissues that are shadowed by strongly-scattering tissue such as the eyes (Hillman et al 2019;Lavagnino et al 2004) and, critically, a direct and bidirectional interference between the imaging system itself and any light stimuli applied for studying zebrafish vision (Vladimirov et al 2014).…”
Section: Figure 5 | 2p Plane-bending To Image the In Vivo Larval Zebrmentioning
confidence: 99%
“…Furthermore, it has been demonstrated [30] that image artifacts are still evident using slow sweeping rates, while they are greatly reduced at higher rates. The pivoting dynamic can be sped up using Acousto-Optic Deflectors (AODs) which do not have any inertial restrictions [31] and allow to generate simultaneously multiple beams at different angles (static multi-angle illumination) or to rapidly sweep a single beam (dynamic pivoting), reaching up to MHz rates [30]. Moreover, AODs can create and sweep two illumination beams in order to leverage the dual rolling shutter mode of several sCMOS cameras [32].…”
Section: Introductionmentioning
confidence: 99%